Dental materials for primary dentition: are they suitable for occlusal restorations? A two-body wear study - Lazaridou, Dimitra; Belli, Renan; Krämer, N.; Petschelt, Anselm; Lohbauer, Ulrich (European archives of paediatric dentistry : official journal of the European Academy of Paediatric Dentistry, 2015)
This was to evaluate the wear resistance of different materials, compomers, resin-modified glass ionomer cements (RMGICs), glass ionomer cements (GICs), used for posterior restorations in primary teeth and to compare the results with the reference material, amalgam.Eight specimens of each material were subjected to two-body wear test, using a chewing simulator. The wear region of each material was examined under a profilometer, measuring the vertical loss (?m) and the volume loss (mm(3)) of the materials.The results showed significant differences of vertical loss and volume loss of the test materials (p < 0.001). Amalgam had the highest wear resistance. Twinky Star (compomer) had the lowest vertical loss and volume loss. There was no significant difference of vertical loss among compomers, Dyract Extra, Dyract Flow and Dyract Posterior. Riva Self Cure (GIC) had no statistically significant difference compared with the compomers (except Twinky Star). No statistically significant difference was found also between Equia (GIC) and Ketac Moral (GIC) with Dyract Extra (Compomer). RMGICs were found to have the lowest wear resistance.For the statistical analysis, the PASW 20.0 (SPSS Statistics, IBM, Chicago) package was used. Means and standard deviations were measured with descriptive statistics and analyzed using one-way ANOVA.Compomers and some GICs, that have moderate wear resistance, may be sufficient for occlusal restorations in primary dentitions.
EVALuna2:24677